Sales of alcoholic beverages by volume, value and per capita 15 years and over, fiscal years ended March 31 - Statistics Canada (Government of Canada, 2017)
This table contains 406 series, with data for years 1950 - 31-MAR-13 not all combinations necessarily have data for all years), and was last released on 2015-05-04. This table contains data described by the following dimensions (Not all combinations are available): Geography (15 items: Canada;Prince Edward Island;Nova Scotia;Newfoundland and Labrador ...), Type of sales (2 items: Total sales;Total per capita sales ...), Type of beverage (4 items: Total alcoholic beverages;Spirits;Wines;Beer ...), Value and volume (2 items: Value in dollars;Volume in litres ...), Type of product (3 items: Total products;Import products;Canadian products ...).